Upaya Meningkatkan Hasil Belajar Passing Atas Bola Voli Menggunakan Media Bola Gantung Pada Siswa SMP Negeri Gudang Arang Merauke - Jori Lahinda; Nancy E. B. Rahangiar; Emanuel Lewar (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
This study aims to improve passing skills for volleyball by using hanging balls as a medium for class VIIIB students of Gudang Arang Merauke State Middle School. This research is a class action research conducted in 2 cycles, each cycle consisting of 2 meetings. Gudang Arang Merauke State, Jalan Pintu Air, Merauke. The subjects of this research were class VIIIB students of Gudang Arang Merauke State Middle School, totaling 23 students consisting of 11 male students and 12 female students. The data collection technique used in learning outcomes contained three aspects. namely: Affective assessment aspect format, worksheet, and psychomotor aspect assessment. In this study, the data analysis technique used was qualitative description analysis. Research skills show that using hanging ball media can improve learning outcomes of passing over volleyball in class VIIIB students of Gudang Arang Merauke Public Middle School, which is marked by increased student learning outcomes in each cycle. In cycle 1 the percentage of students who complete is 74% or 17 students completed experience an increase in cycle 2 value data 80% is 21 students or those who complete learning, then there is an increase of 91% in cycle 2 the increase in completeness from cycle I to cycle II is 91%